DAMPAK AKTIVITAS PERTAMBANGAN EMAS SKALA KECIL TERHADAP DINAMIKA LINGKUNGAN SOSIAL DESA PASIRGOMBONG - Nadya Kharima; Haya Nuramaliza; Miranda Zahra Syafrika Parameswari; Satrio Pandu Nugroho; Agung Rivaldi (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This study aims to describe and analyze the impact of Small-Scale Gold Mining (SSGM) activities on the social life of the community in Pasirgombong Village. The focus of the study includes patterns of socio-economic change in the community, lifestyles, and the potential for social conflict that may arise. The research uses a descriptive qualitative approach with data collection techniques through direct observation and in-depth interviews with several key informants, namely active miners and community leaders. Data analysis is carried out qualitatively through data reduction, data presentation, and conclusion drawing. The results of the study show that Small-Scale Gold Mining (SSGM) has become a more promising alternative livelihood compared to traditional agriculture and has changed the socio-economic orientation of the community. The presence of mining activities increases income, access to education, and quality of life. Despite socio-economic shifts, communal values and social solidarity remain strong. Conflicts over land ownership and profit sharing are generally minor and are resolved through traditional mediation. Small-Scale Gold Mining (SSGM) is a social phenomenon that reshapes community relationships and structures, with communities able to adapt and manage conflicts through local norms to ensure social stability.